2017
DOI: 10.1002/adv.21833
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of carbon black and carbon nanotubes on the electrical resistivity of poly(butylene‐terephthalate) nanocomposites

Abstract: In this study, novel electrically conductive polymeric nanocomposites based on polybutylene terephthalate (PBT) filled with commercial carbon black (CB) and carbon nanotubes (CNTs) at different relative ratios have been investigated. Field emission scanning electron microscope (FESEM) analysis revealed how a good nanofiller dispersion was obtained both by introducing CB and CNT. Melt flow index measurements highlighted that the processability of the nanocomposites was heavily compromised at elevated filler amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…In our previous work on PA12 nanocomposites an electrical resistivity value of 1.8 × 10 3 Ωˑcm was obtained by adding a mixture of carbon black and carbon nanofibers at a total filler loading of 4 wt%. The industrial partner (UFI Innovation Center Srl) involved in this research indicated a resistivity value equal or lower than 10 3 Ωˑcm as the technical requirement to obtain non woven filters that could be effectively heated through Joule effect . Therefore, further efforts will be made in the future to improve nanofiller dispersion and to achieve higher electrical conductivity values.…”
Section: Resultssupporting
confidence: 59%
“…In our previous work on PA12 nanocomposites an electrical resistivity value of 1.8 × 10 3 Ωˑcm was obtained by adding a mixture of carbon black and carbon nanofibers at a total filler loading of 4 wt%. The industrial partner (UFI Innovation Center Srl) involved in this research indicated a resistivity value equal or lower than 10 3 Ωˑcm as the technical requirement to obtain non woven filters that could be effectively heated through Joule effect . Therefore, further efforts will be made in the future to improve nanofiller dispersion and to achieve higher electrical conductivity values.…”
Section: Resultssupporting
confidence: 59%
“…We simulate systems at the nanoscale where CNTs are about 28 nm long, that is a small size compared to the ones employed experimentally whose length ranges between 1-100 mm. 53,61,92,[100][101][102][103][104] Systems of sizes closer to the experimental one can be simulated, but at the cost of losing an accurate description of the main factors affecting and inuencing the Joule effect. For this reason, in this work we chose to focus on a scale that allows us to perform wide screenings of parameters such as the interaction with the matrix, the nature of the matrix and the Joule effect measurement conditions like applied voltage, ller concentration, ller morphology.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%
“…In recent years, polymer nanocomposites (PNC) have attracted great academic and industrial research effort. 1,2 Nanocomposite technology expands the performance area of traditional composites and paves the way for completely new applications of polymers. The advantages of nanocomposites come from the properties of nanofillers.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these, PNCs exhibit various properties such as high mechanical properties, electrical-thermal conductivity, high thermal stability, flame retardancy, even at low filler loading levels. 2,3 Over the last decades, various nanofillers, such as, carbon nanofibers, 4 clay, 5 carbon black, 6 carbon nanotubes, 7 metal nanoparticles, 8 graphene 9,10 have been used frequently for reinforcing of polymer matrices. Among these fillers, graphene (Gr) has attracted considerable attention since its discovery in 2004.…”
Section: Introductionmentioning
confidence: 99%